The Impact of the Coronavirus Disease-2019 Pandemic on the Psychological Status and Quality of Life of Myasthenia Gravis Patients - Stojanov, Aleksandar (Ann Indian Acad Neurol, 2020)
OBJECTIVES: The coronavirus disease 2019 (COVID-19) is the largest pandemic of our times. We wanted to investigate the impact of COVID-19 pandemic on the psychological status, quality of life (QoL) and quality of sleep (QoS) of myasthenia gravis (MG) patients. METHODS: Data on the epidemiological and clinical characteristics of MG were collected. We used a self-designed questionnaire (consisting of 12 questions), a revised 15-item Myasthenia Gravis Quality of Life Questionnaire (MGQOL15r), a 36-item health survey of the Medical Outcomes Study Short Form (SF36), Pittsburgh sleep quality index (PSQI), Hamilton scales for the assessment of anxiety (HAM-A), and depression (HAMD) were used. We reassessed patients who were tested three years ago using the same questionnaires. RESULTS: The study included 64 MG patients. We noticed a statistically significant difference between the results obtained three years ago and the results from April 2020 in PSQI scores (P < 0.01). MGQOL15r, SF36, and PSQI scores correlate with severe clinical manifestation, high scores on HAM-A and HAM-D (P < 0.01). Higher scores on HAM-D and fear that MG symptoms will be worse if the patient gets an upper respiratory infection were independent predictors of the lower SF36 scores. Regarding MGQOL15r-independent predictors of the higher score were higher scores on HAM-D. CONCLUSIONS: There is a significant impact of the COVID-19 epidemic on the psychological status and especially on the quality of sleep of MG patients. Healthcare organizations need to provide professional therapeutic advice and psychosocial support for this population of patients during the pandemic.